Management of congenital airway obstruction due to mandibular hypoplasia using distraction osteogenesis: experience from a specialized institute in Lima, Peru - Oré Acevedo, Juan Francisco (2024)
Bilateral mandibular hypoplasia is the leading cause of airway obstruction in children and can result in both  respiratory  and  digestive  distress.  Treatment  often  involves  mandibular  distraction  osteogenesis,  a  technique  that  increases  the  anteroposterior  length  of  the  mandible.  This  study  aimed  to  share  the  experiences of a pediatric specialty institute in Lima, Peru, using distraction osteogenesis to restore airway and  digestive  function.  Data  on  sociodemographic  and  clinical  (pre-and  postoperative)  information  were  collected  from  patients  who  underwent  bilateral  mandibular  distraction  between  2016  and  2022.  Seventeen  patients  were  included,  53  %  of  whom  were  between  1  and  11  months  old.  All  patients  required care in the Intensive Care Unit, with 58.8 % (9/17) needing orotracheal intubation and 41.2 % (8/17) undergoing tracheostomy. The procedure resulted in anatomical and functional improvements in both the airway and digestive system by increasing the anteroposterior distance of the mandible. These findings suggest that distraction osteogenesis is an effective approach for managing airway obstruction caused by mandibular hypoplasia in pediatric patient.